Język prowokacji w mediach alternatywnych na przykładzie radia internetowego KonteStacja - Nocuń, Rafał (Forum Lingwistyczne, 2016)
Language of Provocation in the Alternative Media on Example of the Online Radio Station KonteStacja The internet has seen an increase in the number of media standing in opposition to the so-called mainstream and questioning the stale state of affairs. The main tool they use to challenge the mainstream is language. To distinguish itself from traditional information providers, online alternative media use it in a highly provocative way. An example of such media is the internet radio KonteStacja. The online community of its supporters has coined a specific language, in which provocation is present in nearly all types of texts. Key words: language of provocation, Internet radio, alternative media, new media<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />